Factors influencing the coping experience of health sciences students in remote learning during the Covid-19 pandemic - Lota, Maria Margarita M.
As a response to the COVID-19 pandemic, many countries resorted to alternative learning activities to continue the conduct of education. Due to the uncertainties of this crisis, remote learning is now considered as the 'new normal' in the education system -especially among countries that have underutilized this platform. With the sudden change in teaching methodologies, institutions are in need of evidence-based solutions to bridge the various gaps present in remote learning. The need for a balanced solution is even more magnified in the context of resource-limited countries and their state-funded institutions, such as in the Philippines. The general objective of the research is to determine the factors in the coping experience among health science students during the COVID-19 pandemic. A descriptive, quantitative, cross-sectional study design was employed for this study. There were 167 undergraduate students, at least 18 years old, enrolled in a health science college who consented and completed the self - administered online survey. Among the technological factors, the availability and access to a stable internet and resources such as computers and learning management systems were essential in the learning of students. Human factors were elemental in influencing the coping experience particularly the teaching methods and course handling of teachers. Moreover, most students agreed that remote learning affected their study habits and attitudes particularly in following a work schedule and accomplishing assigned tasks that resulted to be overburdened and stressed with schoolwork. There were several advantages and disadvantages of remote learning recognized by the students. But majority disagreed to continue the implementation of remote learning after the COVID-19 pandemic. The identified psychosocial factors that contributed to the stress and anxiety of the students include a combination of concerns on health, workload, deadlines, school delay, and being isolated. Overall, the respondents want the pandemic to end soon and were prepared to go back to the traditional face - to-face which remained to be the preferred mode of learning. The experience of students with remote learning during the COVID-19 pandemic provides valuable data to understand their way of coping with a new educational system. The realization gained from these findings, leads to the importance of preparing a resilient education system that also considers the learning capacity and mental health of students to cope with a new instructional strategy.